2018
DOI: 10.3389/fpsyg.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

The Wellbeing of Italian Peacekeeper Military: Psychological Resources, Quality of Life and Internalizing Symptoms

Abstract: Working as a peacekeeper is associated with the exposure to acute and/or catastrophic events and chronic stressors. Hence, the meager literature about peacekeepers’ wellbeing has mainly analyzed Post-Traumatic Stress Disorder (PTSD). This study aims to deep the analysis of the wellbeing of peacekeepers military. Based on the few studies on this population, we hypothesized that Italian peacekeeper military officers and enlisted men (n = 167; 103 males, 6 females, 58 missing) exhibit lower levels of internalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Scholars have analyzed work in many aspects, such as the psychological health and well-being associated to jobs characterized by high stress, like those of military personnel (e.g., [1][2][3]) and healthcare professionals (e.g., [4][5][6]). Moreover, many researchers have been interested in the effects of the ergonomic and structural aspects of the job (e.g., [7][8][9]) and the influence that physical and mental health problems may have on work (e.g., [10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have analyzed work in many aspects, such as the psychological health and well-being associated to jobs characterized by high stress, like those of military personnel (e.g., [1][2][3]) and healthcare professionals (e.g., [4][5][6]). Moreover, many researchers have been interested in the effects of the ergonomic and structural aspects of the job (e.g., [7][8][9]) and the influence that physical and mental health problems may have on work (e.g., [10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been noted in the literature that peacekeepers often stand to benefit professionally from the experience [26]. Peacekeepers also largely report their duties to be satisfying [27] and studies have shown that the experience of peacekeeping has a beneficial effect on quality of life [28]. With this in mind, cyber peacekeeping may be attractive to civilians who are looking for both job satisfaction and a level of professional development that otherwise might not be open to them.…”
Section: A Finding Cyber Expertisementioning
confidence: 99%
“…In Italy the so-called "reconstruction programs" addressed all aspects of rehabilitation (including physiotherapy, curative workshops and vocational therapy) [52]. On the other hand, it has been recently reported that, despite working as a peacekeeper which is associated with the exposure to acute and/or catastrophic events and chronic stressors, Italian peacekeeper soldiers exhibit lower levels of internalizing symptoms (i.e., PTSD, depression, general anxiety, obsessions, and somatization) and have higher levels of quality of life (i.e., higher life satisfaction and lower general stress), as compared to a control group [53]. In this context, in addition to the health property of the Mediterranean lifestyle, Mediterranean diet has been suggested as a natural, non-pharmacological nutraceutical for healthy ageing [54,55] and metabolic syndrome prevention [56].…”
Section: Introductionmentioning
confidence: 99%